(untitled) (Third Sector Social Economic Review, 2013)
Psychological Harassment at Work (PHaW) continues to work through increasingly with fiercely competitive climate by reason of the efforts to increase the efficiency as a fashion concept in professional life. Even though it is substantially affirmed that technology gives the facilities to human life, progress of the technology also restricts the civil liberty zones of the people and transforms the living and work spaces to “Big Brother House”. By this study, master’s field surveys regarding the PHaW were put through the content analysis and the fact of PHaW was explicated how to handle in the field of Turkish academy and presence and level of relationship between PHaW and demographic characteristics was interrogated. Population of this study are 139 dissertations and master’s thesises recorded in Turkish Supreme Education Council’s electronic national thesis archivist regarding PHaW prepared in Turkey during 7 years between 2004 and 2010. There were 93 thesises which were permitted by Turkish Supreme Education Council’s electronic national thesis archivist to download computer on point within 139 hesises. Then, 30 thesises were selected according to aim of this study within 93 downloaded thesises.